Mastering Microsoft Endpoint Manager and Intune - Sequeira, Anthony; Goodwin, Sophia (Packt Publishing, 2024)
Delve into the essentials of Microsoft Endpoint Manager, the robust platform that integrates Microsoft Endpoint Configuration Manager and Microsoft Intune to provide comprehensive management of endpoint devices. Begin your journey with an overview of the product, understanding its components and the advantages of co-management. Learn about the various enrollment options and master the methods for enrolling devices, ensuring a flexible and user-friendly management environment. Progress into the deployment and management of Windows clients, exploring diverse methods and subscription-based activations within Microsoft Intune. Understand the importance of managing Windows updates and leveraging Intune's powerful tools to maintain system integrity. As you advance, discover the intricacies of configuring and securing endpoints through configuration profiles, security, and compliance policies, and implementing security baselines to bolster your organization's security posture. Finally, focus on deploying and managing applications seamlessly using Microsoft Intune, and explore additional features like troubleshooting and advanced client security measures. This course equips you with the knowledge and skills to proficiently manage and secure your organization's endpoint devices, data, and applications.